Oil price, trade openness, current account balances and the official exchange rate in Nigeria. (25th July 2019) - Longe, Adedayo Emmanuel; Muhammad, Shehu; Ajayi, Patricia Iyore; Omitogun, Olawunmi
Abstract: Since a larger percentage of government revenue are generated from crude oil trade, the fluctuations in the price of oil have always been influencing the budget financing in Nigeria. Also, investment decisions and trade cost are been influenced by the status of the oil price. The study investigates the relationship between oil price, trade openness, current account balances and official exchange rate in Nigeria using secondary data from 1980 through 2016. The non‐linear auto‐regressive distributed lag (NARDL) was used to analyse the short‐run and long‐run link between the variables. From the findings, it was established that in the short run and long run, trade openness negatively impacts on the official exchange rate of naira to dollar in Nigeria. The consumer price index positively and significantly influences exchange rate value in Nigeria in the short run and long run. Positive changes in oil price impacted negatively on official exchange rate in the short run, but in the long run had a positive impact. Negative changes in the price of oil have a positive insignificant and negative significant impact on official exchange rate in the short run and long run, respectively. The error correction result verified that the variables (trade openness, current account, oil price and consumer price index) correct 91 per cent deviations of exchange rate from short‐run equilibrium back to equilibrium in the long run. The study concludes that trade policy in Nigeria is not in favourable direction of official exchange rate in Nigeria. Also, positive changes in oil price and current account balances are strong determinants of the Nigerian official exchange rate of naira to dollar in the long run. Therefore, it is recommended that trade policies should be reviewed in Nigeria towards enhancing other sectors that would add more value to naira.